Quick determination of included angles distribution for miscut substrate. (July 2016) - Wang, Jinxing; Hao, Jinghua; Mu, Juyi; Li, Tengfei; Wang, Jing; Cao, Pin
Abstract: A simple method which can be performed with general laboratory facility is described for quickly determining the included angles distribution (including miscut angle) between the crystal plane and sample plane for a miscut substrate. This method is based on the rocking curve measurement of High-resolution X-ray diffraction (HRXRD). After easily measuring and calculating values of two included angles ( θ 1 and θ 2 ) between the crystal plane and sample plane at two arbitrary mutually perpendicular azimuths of the sample plane by HRXRD, all included angles at arbitrary azimuths of the miscut substrate can be quickly calculated. Further, the value of miscut angle ( θ max ) can be determined and its specific azimuth position on sample plane can be also easily found. Besides, since original azimuthal measurements of θ 1 and θ 2 may be situated on different positions of the sample plane, the possible condition is finally classified as four types. And then, the curves of miscut angle and azimuthal orientation under four different conditions are described in detail, respectively and their computational formulas are also distinguished carefully.